Analysis of The Profitability of Traditional Tuna Processing (Boiling) Businesses in Mataram City - Aprilina, Anggun Rizki Siami; Junaidi, Muhammad; Noviyanti, Rinda (Jurnal Biologi Tropis, 2026)
One of the leading fisheries products in Mataram City is boiled skipjack tuna (pindang ikan tongkol). This study aims to identify the potential and procurement of raw materials for boiled skipjack tuna processing in Mataram City and to analyze the financial feasibility (business profitability) as well as the development strategies of traditional boiled skipjack tuna processing enterprises. Data were collected using a descriptive quantitative approach through surveys, interviews, and documentation. Data analysis employed business feasibility analysis, including profitability, R/C ratio, ROI, and Payback Period (PBP), as well as SWOT analysis. The results indicate that traditional boiled skipjack tuna processing enterprises in Mataram City have considerable potential and promising sustainability prospects. The procurement of skipjack tuna raw materials is sourced from local fishermen, surrounding areas, and the availability of cold storage facilities, which play a crucial role in maintaining production continuity. The boiled skipjack tuna processing business in Mataram City is proven to be feasible and profitable for further development. This is reflected in the average annual profit, which reaches IDR 47,964,060 for micro-scale enterprises and IDR 141,405,000 for small-scale enterprises. The R/C ratio is 1.06 for micro-scale enterprises and 1.04 for small-scale enterprises. The ROI values are 28% for micro-scale enterprises and 21% for small-scale enterprises, with a very short Payback Period of 14–18 days. The business development strategy places boiled skipjack tuna processing enterprises in a strategic position that enables the implementation of aggressive strategies through the optimization of internal strengths and the utilization of external opportunities to enhance competitiveness and business sustainability.